Greenland women seek compensation over involuntary birth control - Cooney, Christie (BBC News, 2023)
Some 4,500 women were fitted with coils as part of attempts to limit the territory's population.
Denmark
Keywords: 2023-10 October; Greenland; Sterilization; Women's Rights